Collaboratives service in public libraries for equal information access / Amalia Lestari ... [et al.] - Lestari, Amalia; Mutia, Fitri; Atmi, Ragil Tri; Fahmi, Faisal; Yuadi, Imam (Faculty of Information Management, 2023)
The inequality of access to information is still experienced by several groups of people, for instance, those with disabilities, those living in rural areas, and people of lower socio-economic status. Public libraries as information centers that have the main role in providing access to information for the public of all sorts of people need to ensure that everyone can access information equally. Cooperation and collaboration with other communities and institutions other than other libraries can be a means for public libraries to create collaborative services that target specific groups of people with specific needs. In the emerging trends of information technology, libraries need to survive by creating innovation and providing better services. This study used a literature review as the method of study. This study aims to explore the needs and the ways for public libraries to create collaborative service by reviewing previous literature regarding collaborative service in various fields. The study is expected to benefit researchers and public librarians to take part to support equal access to information.